IMPLEMENTATION OF INFORMATION AND COMMUNICATION TECHNOLOGY IN EFFORTS TO IMPROVE ACADEMIC ADMINISTRATIVE SERVICES IN STKIP ARRAHMANIYAH - Raden Ahmad Hilmi Khoiri; Endang Herawan; Nani Hartini (Universitas Negeri Medan, 2023)
This study intend to determine the relation and efectivity between Information and Communication Technology Utilization and academic administration services. The method used in this research is correlation using a quantitative approach. The population in this research were 80 STKIP Arrahmaniyah students who felt and received academic administration services. Based on the results of the correlation analysis between the variables of the use of Information and Communication Technology with the variables of Academic Administration Services, obtained rcount value of 0.085. From the calculation results, it is obtained that the value of t count (7.5) ≥ t tab (1.99), then H0 is rejected, H1 is accepted. It can be concluded that there is a relationship between the use of The Relationship Between Information and Communication Technology Utilization and Academic Administration Services. Through this research, the authors suggest that the staff of the Academic Administration STKIP Arrahmaniyah continue to improve their performance. Institutions must maintain other things that motivate the performance of BAK staff to continue to improve. BAK staff in carrying out their noble duties in the institution can be motivated. The findings of the study demonstrate that the use of ICT has improved STKIP Arrahmaniyah's academic administration services in terms of efficiency and effectiveness. It has been discovered that the usage of academic information systems, online portals, and electronic communications has aided in speeding up information accessibility, decreasing document processing times, and enhancing stakeholder contact. Therefore, this study offers empirical proof of the significance of integrating ICT into STKIP Arrahmaniyah's academic administration. Other educational institutions who want to use ICT to enhance their academic administration services should use these findings as a guide. Additionally, this study contributes to the body of knowledge on ICT use in academic administration and higher education.